INOVASI PEMBUATAN SABUN CUCI PIRING BERBAHAN ALAMI DI DESA BANDAR JAYA KECAMATAN TRAMANG JAYA KABUPATEN MUKOMUKO, BENGKULU - Ferry Lismanto Syaiful; Risma Anindia (Jurnal Hilirisasi IPTEKS, 2023)
Dish soap cleanses for dirt and food scraps, generally made of chemicals and vegetable/animal fatty acids. However, the problem with dish soap is that irritant contact dermatitis often occurs. To overcome this, it is necessary to have herbal/natural dish soap that can moisturize the skin, be smooth and soft, and have a distinctive aroma to the dish soap. This activity aims to provide education on making soap made from environmentally friendly natural ingredients, increase knowledge and skills for the community in making herbal/natural dish soap, and create new business opportunities to improve people's welfare in Bandar Jaya Village, Mukomuko Regency. This activity was carried out in Bandar Jaya Village, Mukomuko Regency. The exercise targets mothers and the community in Bandar Jaya Village, Bengkulu. The methods used in this activity are counseling, training, and evaluation. This training activity for making natural dish soap is carried out by providing exposure and direct practice to the community regarding the manufacture of dish soap. The results obtained from this activity were: participants enthusiastically participated in this activity, so they could increase their knowledge and skills in utilizing natural materials to be processed into dish soap. From this activity, it can be concluded that the manufacture of dish soap made from natural ingredients does not require large quantities, and using natural ingredients is also more guaranteed for health safety. Making dish soap from natural ingredients can also be an alternative for washing dishes and minimizing the cost of buying dish washing soap for the community.